Strategi Meningkatkan Kesejahteraan Pengelola Warung Madura Di Kawasan Sidosermo, Surabaya - Ilham, Raden Bagus Mohammad Rifki Febrika; Iswati, Iswati; Fitriyasari, Anis (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to investigate the development strategies of Warung Madura and their impact on the well-being of the managers in the Sidosermo area, Surabaya. Data was collected through interviews with Warung Madura managers and analyzed using descriptive qualitative methods. Purposive sampling was used to select relevant informants. The results show that the development has positively contributed to improving the managers' well-being through increased income and economic stability. Additionally, good cooperation and communication among the warung managers have strengthened social relationships and harmony within the local community. The study also discusses the implications of development on the harmony between Warung Madura managers and the surrounding community. It is hoped that this research provides useful insights for formulating policies and programs that support the development of Warung Madura and strengthen its role in the local economy. In conclusion, appropriate development strategies can enhance well-being and strengthen social networks among warung managers.